TRANSFORMASI MANAJEMEN SDM ERA 5.0: SINTESIS KOMPETENSI HOLISTIK, PENGEMBANGAN BERKELANJUTAN, DAN PENILAIAN KINERJA BERBASIS DATA - Edi Faisal Harahap (Jurnal Mahkota Bisnis (Makbis), 2026)
Background: The transition from the Industry 4.0 era to Society 5.0 demands a fundamental reconceptualization of Human Resource Management (HRM). While Industry 4.0 focused heavily on automation and digital technology integration, Society 5.0 repositions humans at the center of organizational sustainability (human-centricity), augmented by Artificial Intelligence (AI) and big data analytics. Existing literature still addresses digital competencies, HR development strategies, and performance appraisal systems in a fragmented manner, without an integrative framework linking the three. Purpose: This study aims to conceptually integrate three primary dimensions of HRM 5.0 transformation: a holistic competency taxonomy, strategic Human Resource Development (HRD), and the evolution of performance appraisal paradigms. Methods: This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 protocol, searching Scopus, ScienceDirect, SpringerLink, SINTA, and Google Scholar for reputable literature published between 2010 and 2026, yielding 32 articles that met the inclusion criteria for synthesis. Results: The synthesis establishes an integrated HRM 5.0 framework consisting of: (1) a holistic competency taxonomy synergizing digital competencies with soft competencies categorized into Managing People, Managing Task, and Managing Self; (2) strategic HRD approaches driven by continuous upskilling/reskilling, HR Analytics integration, and cultural-structural barrier mitigation; and (3) the evolution of performance appraisal systems from retrospective annual reviews to Continuous Performance Management measuring Employee Digital Performance (EDP) embedded within ethical and human-centric values. Conclusion: These three pillars are mutually reinforcing and form an integrative, human-centric, adaptive, and sustainable HRM 5.0 conceptual framework that offers a strategic roadmap for academics and HRM practitioners navigating digital transformation.